151k views
5 votes
Solve the equation by combining like terms: 3x-5+12-2x=12

User Slashsharp
by
4.3k points

2 Answers

9 votes
3x-5+12-2x=12
X+7=12 (by combining like terms you have your X’s and your regular numbers. So in this equation we have 3x and -2x as like terms and -5 and 12 as like terms. We combine them to simplify the equation. So by combing 3x and -2x, 3+(-2x), we get 1x or just x. Then we combine -5 and 12, -5+12=7).
X+7=12
-7 -7
X=5
Good luck and I hope this helps!
User Dynex
by
4.6k points
3 votes

Answer:

482

Explanation:

3x-5=178+12=82-22x=482

User Mike Burba
by
4.3k points